2022
DOI: 10.52403/ijhsr.20220722
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Complete Blood Counts Parameters of Occupational Radiation and Non-Radiation Professionals from Three Teaching Hospitals in South-South Nigeria

Abstract: Background: The exposure of radiation workers to ionizing radiations, especially in medical field has increased due to the use of advance technological equipment in the diagnostic radiology and radiotherapy departments. This study is aimed at evaluating the effects of ionizing radiation on CBC parameters of medical radiation workers in South-South, Nigeria. Materials and Methods: This comparative cross-sectional study was conducted in three teaching hospitals to include 39 radiation workers and 39 non-radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…This worker presented erythema on the hand and face, but the dose estimate did not reach the limits for deterministic effect, not characterizing relational causality. [29] Thus, the present study corroborates what was reported by different authors [5,10,13,23] and national and international organizations [6,8] as it does not identify a p. 16 PAG statistically significant relationship between the leukocyte and platelet counts of CBC tests and the radiation dose levels of HCW in diagnostic and interventional radiology.…”
Section: P 8 Pagsupporting
confidence: 92%
See 1 more Smart Citation
“…This worker presented erythema on the hand and face, but the dose estimate did not reach the limits for deterministic effect, not characterizing relational causality. [29] Thus, the present study corroborates what was reported by different authors [5,10,13,23] and national and international organizations [6,8] as it does not identify a p. 16 PAG statistically significant relationship between the leukocyte and platelet counts of CBC tests and the radiation dose levels of HCW in diagnostic and interventional radiology.…”
Section: P 8 Pagsupporting
confidence: 92%
“…Leukopenia and thrombocytopenia were identified in only 1.09% (95% CI, 0.84 -1.39) of CBC tests for leukocyte count and 2.13% (95% CI, 1.78 -2.53) for platelet count. Association of abnormal immunological responses to accumulated exposure in low doses has no significance as stated in the studies by Forslund et al [21], Gelas et al [22], Zare et al [5] and Orji et al [23].…”
Section: P 8 Pagmentioning
confidence: 99%